PEDAGOGICAL MODEL FOR DEVELOPING FOREIGN LANGUAGE COMPETENCE AMONG MEDICAL EDUCATION STUDENTS - Tuychibayeva Maftuna Bakhodirovna (Scholars Digest Publishing, 2025)
This article examines the process of developing foreign language competence among medical students from a pedagogical perspective. In the context of globalization and international integration, proficiency in foreign languages, particularly English, has become an essential component of medical education. It is required not only for accessing scientific literature and participating in international conferences but also for effective professional communication and research activities. A pedagogical model was developed that integrates target, content, methodological, technological, and assessment components into the language training process. The research employed theoretical, comparative, and empirical methods, including pedagogical modeling, observation, experiments, surveys, and interviews. Results demonstrated that communicative approaches, CLIL (Content and Language Integrated Learning), interdisciplinary integration, and innovative technologies significantly enhanced students’ linguistic competence, motivation, and ability to apply foreign languages in professional contexts. Despite challenges such as limited resources, varied proficiency levels, and insufficient teacher training, the model proved effective in preparing students for international collaboration and professional growth.
Keywords: Medical education, foreign language competence, pedagogical model, communicative approach, CLIL, interdisciplinary integration, innovative technologies, professional communication, medical terminology.